Customer Engagement Around Cultural and Creative Products: The Role of Social Identity - Zhang, Zaiyu; Li, Wenjia (Frontiers in Psychology, 2022)
Along with the increasing trend of transactions occurring on social media, the consumption of Chinese cultural and creative products increased even against the background of the Covid-19 pandemic. In this context, this article aims to analyze the relationships between virtual community–based social identity and cultural and creative product customer engagement behaviors. To this end, social identity theory and customer engagement behavior theory were applied to Zhou’s (2009) model. Structural equation modeling (SEM) was conducted using data from 520 self-administered questionnaires from online virtual community members. The results show that social identity had a significant effect on customer knowledge behavior, participation behavior, and influencer behavior. Moreover, influencer behavior mediates the effect of social identity on purchase intention. The study also identified gender differences in the mediation for influencer behaviors. Our results suggest that women are more sensitive to influencer behaviors than men, thus generating more purchase behaviors.